2021
DOI: 10.1111/spc3.12634
|View full text |Cite
|
Sign up to set email alerts
|

Perceived responsiveness across cultures: The role of cultural fit in social support use

Abstract: Perceived responsiveness plays a key role in social support interactions. Past research shows that people are more likely to seek support when they perceive that close others will be responsive to their needs, and that social support is most effective when it is perceived as responsive. However, theoretical models and measures of perceived responsiveness, and conceptualizations of responsive support, have been based primarily on the norms and values of individualistic cultures and may not generalize to collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 86 publications
(120 reference statements)
2
16
0
Order By: Relevance
“…On the one hand, help-seeking can be a largely advantageous strategy to help people achieve goals or solve problems; on the other hand, help-seeking can result in relational strain and thus incur pertinent intra- and interpersonal costs. The current results support our hypothesis that help-seeking tendencies confer more well-being benefits when the outcomes implicated in help-seeking are more aligned with the culture’s mandates, in line with previous research suggesting that culture has a normative influence on well-being (Kitayama, Karasawa, et al 2010; Wu, Kim, and Collins 2021). These findings are also in line with previous research suggesting that Asian Americans experienced more relational concerns (Taylor et al, 2004) and psychological stress after seeking help (Taylor et al, 2007).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…On the one hand, help-seeking can be a largely advantageous strategy to help people achieve goals or solve problems; on the other hand, help-seeking can result in relational strain and thus incur pertinent intra- and interpersonal costs. The current results support our hypothesis that help-seeking tendencies confer more well-being benefits when the outcomes implicated in help-seeking are more aligned with the culture’s mandates, in line with previous research suggesting that culture has a normative influence on well-being (Kitayama, Karasawa, et al 2010; Wu, Kim, and Collins 2021). These findings are also in line with previous research suggesting that Asian Americans experienced more relational concerns (Taylor et al, 2004) and psychological stress after seeking help (Taylor et al, 2007).…”
Section: Discussionsupporting
confidence: 91%
“…Some may argue that emotional help-seeking that involves more self-disclosing compared to problemfocused or instrumental help-seeking (Skinner 2003;Ve ´lez et al 2016) can possibly promote rather than harm relational harmony and thus be deemed more beneficial for interdependencepreferring cultures like Japan. However, existing works suggest that this may not be the case (for a review, see Wu et al 2021). For example, in Kim, Sherman, and Taylor's (2008) work examining cross-cultural differences in supportseeking, the results showed that Asians are less likely to benefit from support that involves disclosing their personal stressful events and feelings of distress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, Asians and Asian Americans are less likely to seek out social support in response to stressors compared to European Americans, with relational and group harmony concerns being the primary reasons for this reluctance [58,[93][94][95]. Thus, whereas people in individualist societies may seek out social support to fulfil personal goals and a desire for self-expression, people in collectivist societies appear to forgo such direct requests due to broader concerns with collective goals and maintaining a harmonious social environment [58,91,96]. However, this evidence does not suggest that those from collectivistic societies do not use or derive benefits from social support.…”
Section: Cross-cultural Differences In Social Support Benefitsmentioning
confidence: 99%
“…Instead, the type of support considered to be most effective may vary, with those from collectivist cultures benefiting from instrumental, implicit and unsolicited support, and those from individualist cultures benefiting from emotional, explicit and solicited support [96]. Whereas explicitly asking for emotional support can be perceived as burdening another individual, implicit support in the form of recognizing the presence of supportive others does not disrupt relational harmony and instead reinforces the presence of a reliable social network [92,96]. Consistent with this idea of cultural fit in social support, Mortenson et al [94] found that European Americans were more likely to seek out emotional support compared to sojourning Chinese students, and Chinese students had a stronger preference for instrumental support than emotional support.…”
Section: Cross-cultural Differences In Social Support Benefitsmentioning
confidence: 99%